2019
DOI: 10.1111/neup.12532
|View full text |Cite
|
Sign up to set email alerts
|

Globular glial tauopathy Type II: Clinicopathological study of two autopsy cases

Abstract: Globular glial tauopathies (GGTs) are four‐repeat tauopathies characterized by the presence of two types of tau‐positive globular glial inclusions (GGIs): globular oligodendrocytic and astrocytic inclusions (GOIs and GAIs). GGTs are classified into three different neuropathological subtypes: Types I, II and III. We report two patients with GGTs – a 76‐year‐old woman and a 70‐year‐old man – in whom the disease duration was 5 and 6 years, respectively. Both patients exhibited upper and lower motor neuron signs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…However, the ratio of GOIs to GOIs/CBs in Type II was less than that in Type III (Figure S1). Although described previously in Type II , the present study confirmed that in all cases of both Types II and III, the number of tau‐positive oligodendroglial inclusions gradually decreased from higher to lower levels in the pyramidal tracts (internal capsule/cerebral peduncle > pons > medulla > spinal cord) (Figure S2).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…However, the ratio of GOIs to GOIs/CBs in Type II was less than that in Type III (Figure S1). Although described previously in Type II , the present study confirmed that in all cases of both Types II and III, the number of tau‐positive oligodendroglial inclusions gradually decreased from higher to lower levels in the pyramidal tracts (internal capsule/cerebral peduncle > pons > medulla > spinal cord) (Figure S2).…”
Section: Resultssupporting
confidence: 89%
“…As described below, three of the cases (cases 1–3) had far fewer GAIs in the cerebral cortex than the other three (cases 4–6), a feature that has already been reported , and is considered a representative example of Type III in the 2013 recommendations . Two of the three Type II cases (cases 1 and 2) have been reported recently elsewhere . The clinical features of these autopsied patients are summarised in Table .…”
Section: Methodsmentioning
confidence: 70%
See 2 more Smart Citations
“…[3][4][5] Although the consensus recommendation encourages the detection and subclassification of GGT subtypes for the future establishment of neuropathological and clinical diagnostic criteria, the subclassification of GGT based on actual neuropathological observation is sometimes difficult, and the GGT subtype may not always directly correspond to the clinical symptoms. 6 Tanaka et al (2019) report that in addition to involvement of the motor cortex and corticospinal tract, GGT Type II is impacted by various other central nervous system regions, including the frontotemporal cortices. 7 Another group reported on GGT with a combination of Type I and II pathology.…”
Section: Introductionmentioning
confidence: 99%